An eye into the 2023 Zambia education curriculum framework: What is there for special and inclusive education in Zambia - Kenneth Kapalu Muzata (Journal of General Education and Humanities, 2025)
The Curriculum Development Centre (CDC) in Zambia, a Directorate under the Ministry of Education, has rolled out the 2023 Education Curriculum Framework to guide education in Zambia, replacing the 2013 framework. Emanating from the 2023 Zambia Education Curriculum Framework, this paper critically analyses special and inclusive education for learners with disabilities in the reviewed curriculum. The paper compares the 2013 curriculum framework to the 2023 one and analyses whether Zambia is progressing in providing special and inclusive education to learners with special education needs. With the help of the QDA Miner qualitative data analysis tool, the study revealed that the content within the two curriculum frameworks is 0.378 similar, a Jaccard coefficient which indicates that the content in the two curriculum frameworks is somewhat similar and not entirely different. Even though there appeared to be an improvement in the 2023 curriculum framework, data by word frequency shows that concepts related to disability and special education need provision are inadequately represented, signalling a continued low-key consideration of education provision for learners with disability. Based on the findings of this study, teachers need capacity building in curriculum adaptations for learners with disabilities and autonomy to modify content, teaching, and learning materials and assessments so that learners with disabilities benefit from the 2023 curriculum goals. Providing the necessary resources for competence-based curriculum implementation is critical for the success of the 2023 curriculum goals.